Volatile Oil of Psidium cattleianum Sabine from the Brazilian Atlantic Forest - Marques, Francisco A.; Wendler, Edison R.; Sales Maia, Beatriz Helena L. N.; Coffani-Nunes, Joao V. [UNESP]; Campana, Juliana [UNESP]; Guerrero, Palimecio G. [UNESP] (Allured Publ Corp, 2008)
The essential oil obtained by hydrodistillation of fresh leaves of Psidium cattleianum Sabine, collected in the Atlantic Forest in southeastern Brazil, was analyzed by GC and GC/MS. The oil had the main constituents alpha-thujene (25.2%), 1,8-cineole (16.4%) and beta-caryophyllene (10.2%).
Keywords: Psidium cattleianum; Myrtaceae; essential oil composition; alpha-thujene; 1,8 cineole; beta caryophyllene